The French Counter-Reformation - Woodcock, Philippa (Church history and religious culture, 2014)
This article discusses the redecoration of the rural French parish church in the French diocese of Le Mans from 1620–1688. Scholars have argued that the diocese’s prolific commissions of terracotta statues and retables represented the impact of the Council of Trent’s drive to educate the clergy and instill in them a sense of connoisseurship; the clergy led the diocese as patrons. Yet, these works of art are also quite particular to the region, suggesting that other factors were responsible for their proliferation. This article examines the statues and retable of St-Léonard-des-Bois, commissioned in c. 1630 and 1684. Using previously unavailable archival material, it proposes two new patrons for these commissions, and reconsiders the motives for clerical and secular leadership in this rural parish. It demonstrates that the rural world was not isolated and it is significant that both patrons came from beyond the parish. The article evaluates the influence upon the statues and retable of the centralising ‘Counter-Reformation’ and local factors such as geography, regional traditions, and local events. It argues that the rural Counter-Reformation had a paradoxical identity. It belonged to wider currents in Catholic Reform, and in the case of St-Léonard, was driven by two patrons determined to create a new position for themselves. However, as both of these commissions were accepted by the church’s fabrique, it is evident that subject choices persistently reflected older traditions, and images responded to very local circumstances.